x^2+6x
f(x)= ----------
x-2
(x-6)(x+2)
f'(x)= --------------
(x-2)^2
(x-6)(x+2)
Aratati ca f'(x)= -------------
(x-2)^2
Răspunsuri la întrebare
Răspuns de
2
f'(x)=![\frac{( x^{2}+6x)'(x-2)-( x^{2} +6x)(x-2)' }{ (x-2)^{2} } \frac{( x^{2}+6x)'(x-2)-( x^{2} +6x)(x-2)' }{ (x-2)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B%28+x%5E%7B2%7D%2B6x%29%27%28x-2%29-%28+x%5E%7B2%7D+%2B6x%29%28x-2%29%27+%7D%7B+%28x-2%29%5E%7B2%7D+%7D+)
=![\frac{(2x+6)(x-2)- x^{2} -6x}{ (x-2)^{2} } \frac{(2x+6)(x-2)- x^{2} -6x}{ (x-2)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B%282x%2B6%29%28x-2%29-+x%5E%7B2%7D+-6x%7D%7B+%28x-2%29%5E%7B2%7D+%7D+)
=![\frac{2 x^{2} -4x+6x-12- x^{2} +6x}{ (x-2)^{2} } \frac{2 x^{2} -4x+6x-12- x^{2} +6x}{ (x-2)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B2+x%5E%7B2%7D+-4x%2B6x-12-+x%5E%7B2%7D+%2B6x%7D%7B+%28x-2%29%5E%7B2%7D+%7D+)
=
=![\frac{(x-6)(x+2)}{ (x-2)^{2} } \frac{(x-6)(x+2)}{ (x-2)^{2} }](https://tex.z-dn.net/?f=+%5Cfrac%7B%28x-6%29%28x%2B2%29%7D%7B+%28x-2%29%5E%7B2%7D+%7D+)
Δ=![16+48 = 64=8^{2} 16+48 = 64=8^{2}](https://tex.z-dn.net/?f=16%2B48+%3D+64%3D8%5E%7B2%7D+)
|
| => (x-6)(x+2)
=
=
=
=
Δ=
Alte întrebări interesante
Engleza,
8 ani în urmă
Geografie,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Franceza,
9 ani în urmă